2014
DOI: 10.2172/1159377
|View full text |Cite
|
Sign up to set email alerts
|

Novel Electrolyzer Applications: Providing More Than Just Hydrogen

Abstract: Despite the fact that many electrolyzer projects have been installed, there is little operational data available to quantify their response and flexibility. Electrolyzers electrochemically separate water into hydrogen and oxygen using electricity as the feedstock. This work explores the operational flexibility of electrolyzers by performing experimental tests on a proton exchange membrane (PEM) and an alkaline electrolyzer. Many applications value flexibility, particularly with the addition of increased interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 13 publications
(17 reference statements)
0
84
0
Order By: Relevance
“…While alkaline electrolyzers are advantageous with respect to their longevity and costs,t he lack in gas purity,s afety,a nd response time has pushed the research and industrial interests towards proton exchange membrane (PEM) electrolysis in the recent years. [7,8] Forwater splitting in PEM electrolyzers,the choice of the oxygen evolution reaction (OER) catalyst employed at the anode has ap rofound impact on the cost, lifetime,a nd efficiency of the device.Iridium is commonly used as aOER catalyst, but is highly priced ($546 per troy ounce) [9] and one of the rarest elements in the earth crust, with an annual production and consumption value of only about 4t o9 tons. [10][11][12] Several approaches have been proposed to overcome the challenges associated with the precious metal OER catalyst such as reducing the particle size,thereby increasing the surface to mass ratio, [13] using electro-ceramic supports, [14,15] or enhancing the phase structure.…”
Section: Thetotalglobalhydrogenproductionvalueisgreaterthan30mentioning
confidence: 99%
“…While alkaline electrolyzers are advantageous with respect to their longevity and costs,t he lack in gas purity,s afety,a nd response time has pushed the research and industrial interests towards proton exchange membrane (PEM) electrolysis in the recent years. [7,8] Forwater splitting in PEM electrolyzers,the choice of the oxygen evolution reaction (OER) catalyst employed at the anode has ap rofound impact on the cost, lifetime,a nd efficiency of the device.Iridium is commonly used as aOER catalyst, but is highly priced ($546 per troy ounce) [9] and one of the rarest elements in the earth crust, with an annual production and consumption value of only about 4t o9 tons. [10][11][12] Several approaches have been proposed to overcome the challenges associated with the precious metal OER catalyst such as reducing the particle size,thereby increasing the surface to mass ratio, [13] using electro-ceramic supports, [14,15] or enhancing the phase structure.…”
Section: Thetotalglobalhydrogenproductionvalueisgreaterthan30mentioning
confidence: 99%
“…While alkaline electrolyzers are advantageous with respect to their longevity and costs,t he lack in gas purity,s afety,a nd response time has pushed the research and industrial interests towards proton exchange membrane (PEM) electrolysis in the recent years. [7,8] Forwater splitting in PEM electrolyzers,the choice of the oxygen evolution reaction (OER) catalyst employed at the anode has ap rofound impact on the cost, lifetime,a nd efficiency of the device.Iridium is commonly used as aOER catalyst, but is highly priced ($546 per troy ounce) [9] and one of the rarest elements in the earth crust, with an annual production and consumption value of only about 4t o9 tons. [10][11][12] Several approaches have been proposed to overcome the challenges associated with the precious metal OER catalyst such as reducing the particle size,thereby increasing the surface to mass ratio, [13] using electro-ceramic supports, [14,15] or enhancing the phase structure.…”
Section: Thetotalglobalhydrogenproductionvalueisgreaterthan30mentioning
confidence: 99%
“…Past research has demonstrated the subsecond response of PEM electrolyzers [24], but this demonstration considered electrolyzers already consuming power at steady state. Electrolyzers starting from a "cold start" (i.e., no power to any balance of plant components) exhibit a longer response time.…”
Section: Characterization Of the Electrolyzer Stackmentioning
confidence: 99%
“…The simulations conducted for DRTS could precisely simulate the real-time dynamics of electric grids and have been solved at a 300 µs time-step. For the fast-loop testing, the simulation comprised a DRTS with a model of the electrolyzer on the basis of characterized data recorded during the stack testing [24]. For these tests, it was expected that the FEC could drive the electrolyzer power consumption such that it would provide support to the voltage and frequency stability.…”
Section: Test Approachmentioning
confidence: 99%